Transformation of Islamic Religious Education Learning in the 21st Century Era in Senior High Schools - Efendi, Sahrul; Salman; Septiana, Yulda Dina; Syamsurizal (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
The transformation of Islamic Religious Education (IRE) learning in the 21st century is a crucial response to rapid developments in technology, information, and educational paradigms. This study aims to examine how Islamic Religious Education learning is transformed in senior high schools to meet the demands of 21st-century education, particularly in fostering critical thinking, creativity, collaboration, communication, and digital literacy among students. Using a qualitative descriptive approach, data were collected through classroom observations, interviews with teachers, and analysis of learning documents. The findings indicate that the transformation of IRE learning is reflected in the integration of student-centered learning models, the use of digital learning media, and the implementation of active and contextual learning strategies. However, several challenges remain, including limited technological infrastructure, varying teacher competencies, and time constraints in curriculum implementation. This study concludes that the transformation of Islamic Religious Education learning in senior high schools requires continuous teacher professional development, institutional support, and adaptive learning strategies to ensure that Islamic values are effectively integrated with 21st-century competencies.